A performatividade das quadrilhas juninas: reminiscências da tradição e a espetacularização da dança - Zaratim, Samuel Ribeiro (2020)
This research discusses about quadrilhas juninas/folk june dances, in the concept of performativity, characterized by the Ação Junina in dance on stage from the introduction of the stereotyped figure of the matuto, to the quadrilhas juninas for competition full of new meanings; known as modern or stylized. The analysis dedicated to this work focused on the quadrilheiros experiences as well as on the different appropriations of the notion of Fazer Junino by the groups of quadrilhas juninas, in order to analyze their performance elaborations under the support of the theory of cultural performances. It is important to note that the terms performance characteristics and performativities, are understood in this study, as elements that constitutes the performances of Cultura Junina. In this context, this research presents the multiple factors tha compound the quadrilhas juninas modernas, among them the process of spectacularization of dance and the festivals, including their continuous processes of updating and reframing. In this work, I consider qudrilhas juninas as a product of the cultural industry that presents diversity in the elaboration of cultural goods in their performances, which, in a certain way, are aligned with the social contradictions of their localities. Simultaneously, the quadrilhas juninas as a social group transcends the festive and cultural dimensions, reaching professional ties and organizational actions that seek technical improvement, which stimulates the competitive attitude and encourages a spectacular perspective. The práticas juninas tell their stories, as they demonstrate their balances and imbalances in Fazer Junino, established by innovation, by the phenomenon of spectacularization and by the ideological clashes over culture in the face of media appeals attributed to the cultural market.